Effects of dietary inclusion of yerba mate (Ilex paraguariensis) extract on lamb muscle metabolomics and physicochemical properties in meat - Lobo, Richard R.; Correia, Banny S B; Peña-Bermúdez, Yuli A.; Vincenzi, Rafaela; da Silva, Caroline M.; Panosso, Leticia L.; Ceribeli, Caroline; Colnago, Luiz A.; Cardoso, Daniel R.; Berndt, Alexandre; Pinheiro, Rafael S B [UNESP]; Bueno, Ives C da S; et al. (Oxford University Press (OUP), 2021)
This study aimed to evaluate the effect of dietary yerba mate (Ilex paraguariensis) extract (YME) on muscle metabolomics and physicochemical properties of lamb meat. Thirty-six uncastrated male lambs (90 d old) were fed experimental diets, which treatments consisted of 0%, 1%, 2%, and 4% inclusion of YME. Animals were fed for 50 d before slaughter. Muscle and meat samples were collected for metabolomics and meat quality analysis, respectively. The experiment was carried out in a randomized block design and analyzed using orthogonal contrasts. There was a quadratic effect of YME inclusion in tenderness (P < 0.05) and a positive linear effect on meat lightness (P < 0.05). No qualitative changes (P > 0.05) on individual metabolites were observed; however, changes in the quantitative metabolic profile were observed, showing that animals fed 1% and 2% of YME have a greater concentration of desirable endogenous muscle antioxidants, with direct impact on metabolic pathways related to beta-alanine metabolism and glutathione metabolism. Therefore, YME dietary supplementation up to 2% of the diet to lambs had little to no effects on the majority of meat quality traits evaluated; moreover, 4% of YME inclusion negatively affected feed intake and meat quality traits.
Keywords: antioxidant; instrumental meat quality; metabolomics; natural additive; tenderness